Reconstruction of the Enforcement of Domestic Violence Law in Divorce Cases: Towards an Integrated Framework for Legal Certainty and Victim Protection in Indonesia - Irawan, Sandra; Fautanu, Idzam; Yanuar Chandra, Tofik Yanuar Chandra (Sahabat Publikasi, 2025)
Domestic violence remains a pervasive legal and social problem in Indonesia, particularly when it intersects with divorce proceedings. Despite the existence of the Domestic Violence Law (UU PKDRT), this study finds that law enforcement remains fragmented between the criminal justice system and the religious court system, producing significant uncertainty for victims who must navigate parallel legal processes. Using a normative-empirical methodological design, this research examines statutory frameworks, judicial decisions, and institutional practices to identify the structural, procedural, and cultural factors contributing to the disjunction between criminal adjudication and divorce litigation. The findings reveal systemic weaknesses, including the absence of integrated evidentiary mechanisms, limited inter-agency coordination, and persistent patriarchal biases that hinder victim-centered protection. These deficiencies not only undermine the effectiveness of domestic violence regulation but also restrict victims' access to meaningful legal remedies. Building on these findings, the study proposes an integrated enforcement model that harmonizes evidentiary use, strengthens institutional coordination, and embeds victim protection into both criminal and family court processes. This reconstructed framework aims to enhance legal certainty, improve procedural coherence, and align national practices with international standards on state due diligence in addressing domestic violence. The study contributes to advancing theoretical discourse on legal harmonization and offers practical policy recommendations for reforming Indonesia's domestic violence and family justice systems.